PENDAMPINGAN PEMBUATAN SABUN CAIR FILTRAT LIDAH BUAYA & DAUN MINT SEBAGAI SABUN ANTISEPTIK PENCEGAHAN COVID-19 PADA KADER & IBU PKK KELURAHAN DASAN CERMEN - Lale Budi Kusumadewi; Ari Khusuma; Agrijanti Agrijanti (Jurnal Pengabdian Masyarakat Multidisiplin, 2021)
Covid-19 is a disease caused by the SARS-CoV-2 virus and has symptoms similar to the common cold, which can progress to severe illness and pneumonia (pneumonia), causing difficulty breathing. One of the basic protective measures for individuals against COVID-19 is to wash their hands with soap and running water. Soap is a cleanser made from oil or fat with a strong base. In the final manufacture of soap, dyes, fragrances and natural ingredients are generally added to improve the characteristics of the soap. Aloe vera is one of the plants that are efficacious for maintaining healthy skin. The specialty of aloe vera lies in its gel which is able to seep into the skin tissue so that it resists losing too much fluid from the skin. The use of antibacterial from synthetic materials can prevent infection, but not a few have side effects such as irritation. To solve community problems related to the spread and control of cases of the spread of COVID 19, the implementation of this community service was carried out in the form of training and assistance in making aloe vera and mint leaf filtrate liquid soap as antiseptic soap for the prevention of COVID 19 in mosque cadres and youth in the Dasan Cermen Asri neighborhood. , Dasan Cermen Mataram City. The results of this activity are in the form of increasing the knowledge and skills of partners in making soap and marketing soap produced online.